2004
DOI: 10.1002/adfm.200304498
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Electron Microscopy and Electron Holography of Organic Solar Cells

Abstract: Organic solar cells are a promising route towards large‐area and low‐price photovoltaic systems. The devices are composed of at least two layers: the hole‐transport layer and the electron‐transport layer. The light absorption can occur in one or both layers. At the interface of the layers the excitons are separated into charge carriers, and every layer deals with one type of carrier. Higher efficiencies of the separation process can be obtained by using a mixed layer containing both materials to obtain a very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Figure 4b shows significant increase in number and crystallite sizes of 15–30 nm in the DAN film prepared at 60 °C, comparable to earlier results 5. No crystalline ZnPc regions can be spot indicating that the amorphous phase of ZnPc is stable at these temperatures, which is in good agreement with reference 9 where stability up to 50 °C is reported.…”
Section: Resultssupporting
confidence: 89%
“…Figure 4b shows significant increase in number and crystallite sizes of 15–30 nm in the DAN film prepared at 60 °C, comparable to earlier results 5. No crystalline ZnPc regions can be spot indicating that the amorphous phase of ZnPc is stable at these temperatures, which is in good agreement with reference 9 where stability up to 50 °C is reported.…”
Section: Resultssupporting
confidence: 89%
“…For 70 nm F 4 ZnPc:C 60 blends (1:1 ratio), there are no peaks visible in the XRD diffractograms (see Figure 10b) that could be associated with organic materials. This indicates that these films are at least X‐ray amorphous, which was also observed by Maennig et al46, 47 using electron diffraction for ZnPc:C 60 blends that were deposited at room temperature. X‐ray studies of similar F 4 ZnPc:C 60 samples where the substrate was kept at 110 °C during deposition revealed that, even then, the blend layers are X‐ray amorphous and no crystal structure could be obtained (data not shown).…”
Section: Resultssupporting
confidence: 79%
“…[17] Both electron and X-ray diffraction confirm the existence of crystalline domains of CuPc and C 60 . Crystalline domain sizes range from 5 nm to 10 nm, similar to those found in homogeneous films of C 60 but smaller than ZnPc crystals obtained by thermal evaporation [18,19] . We obtained similar TEM images of [CuPc(3.1 nm)/C 60 (3.1 nm)] 17 , where the crystallites are similar in shape but have slightly smaller sizes, as expected.…”
mentioning
confidence: 85%
“…2b), where the crystalline phase separation is limited. [4,5,18,19,22] As shown in Figure 2c, the surface morphology of the same [CuPc(6.1 nm)/C 60 (6.1 nm)] 10 film observed by AFM shows the crystalline texture with an rms roughness of 12.7 nm, reflecting the roughing effect (c.f. Fig.…”
mentioning
confidence: 89%